Evaluation of the Effect of Topical Prostaglandin Analog Treatment on Orbital Structures in Open-Angle Glaucoma with Computed Tomography - Durmuş Ece, Berire Şeyma; Yozgat, Zübeyir; Bayramlı, Hüseyin; Ece, Bunyamin; Aydin, Sonay (MDPI AG, 2024)
Background/Objectives: This study aims to evaluate the computed tomography (CT) scans of glaucoma patients using prostaglandin analogs (PGA) in one eye, investigate findings associated with prostaglandin-associated periorbitopathy (PAP), and compare these findings with those of the contralateral eyes. Methods: Patients with open-angle glaucoma who had CT images of the orbital region taken for another reason at least one month after starting PGA treatment in one eye were included in the study. Enophthalmos measurements from thin-slice CT images, along with 3D volume measurements of orbital fat tissue, periorbital muscles, and the optic nerve, were performed. Ophthalmological examination findings and treatment information were collected. The values were compared with those of the contralateral eyes of the same patients not using PGA. Intraclass correlation coefficients (ICCs) were computed to evaluate measurement repeatability. Results: Forty patients were included in the study. Among them, 29 (72.5%) used latanoprost, 9 (22.5%) used bimatoprost, and 2 (5%) used travoprost. The mean enophthalmos values on the treated side (15.5 ± 2.0 mm) were lower than on the untreated side (16.1 ± 1.4 mm), but this difference was not statistically significant (p = 0.07). In 29 patients (72.5%), enophthalmos measurements were smaller on the treated side, with 7 patients (17.5%) showing a difference of 2 mm or more. No significant correlation was found between the duration of PGA use and enophthalmos measurements (p = 0.768 r = −0.048). Additionally, no significant differences were found in orbital fat volume, total extraocular muscle volume, and optic nerve volume (p > 0.05). ICC values demonstrated excellent reliability (ICC > 0.75) for all measurements. Conclusions: We did not find significant differences in enophthalmos measurements, orbital fat volume, total muscle volume, and optic nerve volume between the PGA-treated and untreated eyes.
Keywords: Article